COVID-19 Impacts on Beaches and Coastal Water Pollution at Selected Sites in Ecuador, and Management Proposals Post-pandemic - Ormaza-Gonzaìlez, Franklin I.; Castro-Rodas, Divar; Statham, Peter J. (Frontiers in Marine Science, 2021)
The COVID-19 pandemic has obliged Governments all around the world to implement confinement and social distancing measures. Leisure and business activities on beaches and in ports have restricted direct and indirect contamination from, for example, plastics, hydrocarbon spillage, microbiological loads, and noise levels. This has led to temporarily improved environmental conditions, and the beaches having conditions closer to Marine Protected Areas. Here we report some impacts that have been studied using local surveys and qualitative observations in Ecuador at the popular beaches and ports of Salinas, Manta, and Galapagos. Satellite data support this information. Online surveys were carried out at critical moments of the pandemic: May (15th) and just after when measures were relaxed a little, but within lockdown in July (21st) 2020. Respondents were asked to compare conditions before and during the pandemic lockdown. Most (97–99%) suggested that beaches had significantly improved from visual observations during confinement. On a scale from 1 (worst) to 5 (best), the beaches of Salinas and Manta respectively were rated 2.2 and 2.8 (less than acceptable) before quarantine, and 4.5 and 4.3 after; results from the second survey (after 18 weeks of restrictions) were much the same. Replies from Galapagos showed a similar trend but with less marked differences. In addition to the beaches having less plastic and garbage, more fish, and large marine organisms, including humpback whales (Megaptera novaeangliae), dolphin (bottlenose, Tursiops truncatus), and manta ray (Manta sp.) were observed near to shore. At Galapagos beaches, turtles, sea lions, and sharks were observed many more times than pre COVID. Quantitative satellite data on Chlorophyl and attenuation coefficient (Kd, 490 nm) support the qualitative survey data that there is an improvement in coastal environment quality. Here we recommend that this unique opportunity resulting from the COVID-19 pandemic is used locally, regionally and globally to construct baseline data sets that include information on physical, chemical, biological, and microbiological factors in coastal zones. These parameters can then help establish an effective Coastal Zone Management Plan based on beach description and quality (water standards, noise pollution), as well as the human dimension (tourist load, cultural heritage, and economic value indices). This data and information gathering ideally should be done before the beaches become more heavily used again as the pandemic recedes.